A comparative study assessing the efficacy and acceptability of anorectal swabs for antenatal GBS screening. (March 2013) - Law, Kenneth S K; Parmar, Priya; Gregora, Michael; Abbott, Jason
Objectives: To assess women's perception of pain and acceptability of low vaginal swab (LVS) and anorectal swab (ARS) for antenatal screening for Group B Streptococcus (GBS), and to compare the detection rate between these tests. Methods: Separate LVS and ARS were collected at the 36-week antenatal visit, either by the patient herself or by her clinician. Acceptability and pain were evaluated on a Likert scale using a standardised questionnaire. Results: A total of 278 women were recruited, with a median gestation of 36.3 weeks (IQR 36–37). Of these women, 96% undertook specimen self-collection. The overall prevalence of colonisation was 64/278 (23%); 52 women had positive LVS results (18.7%), and an additional 12 (5.5%; 95% CI 2.5–8.5) were negative on LVS but positive on ARS. Most women rated LVS (99%) and ARS (92%) to be either 'pain-free' or causing 'mild discomfort', and found the LVS (90%) and ARS (84%) to be either 'totally acceptable' or 'somewhat acceptable'. Conclusions: The addition of an ARS resulted in an enhanced GBS positive rate, and most women found the test acceptable.